The Effect of Tax Avoidance, Managerial Ownership, Profit Management on Company Value - Prasetya, Lambang; Faisol, Faisol; Sugeng, Sugeng (Proceeding Kilisuci International Conference on Economic & Business, 2023)
Research Aim : Management can practice earnings management by carrying out tax avoidance to increase profits and the value of the company whose shares it owns. Investors as owners of capital must pay attention to the financial performance of a company in increasing funds in its investment, because earnings management can be carried out by managerial parties through tax avoidance so that the company's performance looks good and attracts investors to buy it. The purpose of this study was to determine the effect of tax avoidance, managerial ownership, earnings management on firm value in case studies of manufacturing companies in the food & beverage sub-sector on the Indonesia Stock Exchange. Research Method : This research was conducted through a quantitative approach using secondary data obtained from the Indonesian stock exchange. The data used in this research is the financial data of 12 companies for 3 years. Data analysis techniques in the form of descriptive statistics, Panel Data Model Selection, classic assumption test, Panel Data Analysis, determinant coefficient and hypothesis testing Research Finding : The results showed that tax avoidance had a significant negative effect on firm value, managerial ownership had no effect on firm value and earnings management had no effect on firm value. Meanwhile, the simultaneous results of tax avoidance, managerial ownership, and earnings management have a significant effect on firm value variables.